The failure rate in reliability: approximations and bounds. (1996) - Cocozza-Thivent, Christiane; Kalashnikov, Vladimir
Abstract : We consider models typical to the area of reliability, and a failure rate function for processes describing the dynamics of these models. Various approximations of the failure rate function are proposed and their accuracies are investigated. The basic case studied in the paper is a regenerative model. Some interesting particular cases (Markov, semi-Markov, etc.) are considered. All proposed estimates are stated in a tractable analytic form. This article is dedicated to the memory of Roland L. Dobrushin.